INDIAN CULTURAL ELEMENTS IN MEERASYAL’S LIFE ISN’T ALL HA HAHEEHEE - Thangalakshmi, Vidhya (International Journal of Research -GRANTHAALAYAH, 2017)
This paper is about the Indian cultural elements in the novel Life Isn’t All Ha HaHeeHeeauthored by MeeraSyal. The characters in the novel have dual identities but they are proud to expose their Indian identity by sticking on to the Indian culture in the host land. Having settled in different countries, it is their wish to adopt the foreign culture but instead they are consistent to follow the homeland culture; even though they belonged to second generation diasporans. The important thing to note in this novel is the characters are happy to glorify their homeland (India) culture, which is typically the Punjabi tradition and customs.